2014
DOI: 10.1039/c4sm01532k
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose facilitates DNA melting: a single-molecule optical tweezers study

Abstract: Using optical tweezers, here we show that the overstretching transition force of double-stranded DNA (dsDNA) is lowered significantly by the addition of the disaccharide trehalose as well as certain polyol osmolytes. This effect is found to depend linearly on the logarithm of the trehalose concentration. We propose an entropic driving mechanism for the experimentally observed destabilization of dsDNA that is rooted in the higher affinity of the DNA bases for trehalose than for water, which promotes base exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Correspondingly, phosphates were down-regulated in groups AA, F, and H in response to the stress of inhibitors (Table 1 ). Furthermore, trehalose is synthesized specially upon different stresses to protect various cellular components, and it can also directly interact with nucleic acids to facilitate melting of double-stranded DNA and stabilize single-stranded nucleic acids [ 65 ]. Hence, the up-regulation of trehalose in groups F, P, and C were consistent with its positive effects.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, phosphates were down-regulated in groups AA, F, and H in response to the stress of inhibitors (Table 1 ). Furthermore, trehalose is synthesized specially upon different stresses to protect various cellular components, and it can also directly interact with nucleic acids to facilitate melting of double-stranded DNA and stabilize single-stranded nucleic acids [ 65 ]. Hence, the up-regulation of trehalose in groups F, P, and C were consistent with its positive effects.…”
Section: Resultsmentioning
confidence: 99%
“…In a previously published report on M. smegmatis it has also been shown that trehalose confers protection during elevated temperature (Woodruff et al, 2004). Trehalose is also an effective protectant of biological macromolecules including DNA (Woodruff et al, 2004; Bezrukavnikov et al, 2014). Trehalose prevents denaturation and aggregation of damaged proteins and thus facilitates their repair at a later stage (Strøm and Kaasen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Optical and magnetic tweezers could normally achieve the mechanical information, conformational changes, and interactions of biomolecules, which were also obtainable through MD simulations. Therefore, some studies used the combination of optical/magnetic tweezers and MD simulation to investigate the structure of biomolecules, which was a significant approach in scientific research. However, apart from the above information, MD simulation was capable of revealing the interfacial binding details from the atomic level, probably critical to some interactions, which was not easy to acquire by optical/magnetic tweezers.…”
Section: Discussionmentioning
confidence: 99%